Trust and trustworthiness in organizations: The role of monitoring and moral suasion (2017)
We ask whether the corporate law provisions establishing that the conduct of the manager is subject to review by the investors (monitoring) and that managers are held to an honorable behavior (moral suasion) can increase trust and trustworthiness in organizations. We answer this question through a laboratory experiment. We find that moral suasion increases the investors' trust. Monitoring also increases trust but only when the manager is not aware of the experimental identity of the monitor. The manager returns more to those investors who trust more but appropriates around 50% of the available resources. The trustworthiness of the manager is, however, unaffected by monitoring or moral suasion. We discuss possible causes of the difference between the investors' expectations regarding the behavior of the manager and the observed behavior of the manager.